Phylogenetic and AlphaFold predicted structure analyses provide insights for A1 aspartic protease family classification in Arabidopsis - Duan, Yanling; Tang, Hao; Yu, Xiaobo (Frontiers in Plant Science, 2023)
Aspartic proteases are widely distributed in animals, plants, fungi and other organisms. In land plants, A1 aspartic protease family members have been implicated to play important and varied roles in growth, development and defense. Thus a robust classification of this family is important for understanding their gene function and evolution. However, current A1 family members in Arabidopsis are less well classified and need to be re-evaluated. In this paper, 70 A1 aspartic proteases in Arabidopsis are divided into four groups (group I-IV) based on phylogenetic and gene structure analyses of 1200 A1 aspartic proteases which are obtained from 12 Embryophyta species. Group I-III members are further classified into 2, 4 and 7 subgroups based on the AlphaFold predicted structures. Furthermore, unique insights of A1 aspartic proteases have been unraveled by AlphaFold predicted structures.For example, subgroup II-C members have a unique II-C specific motif in the C-extend domain, and subgroup IV is a Spermatophyta conserved group without canonical DTGS/DSGT active sites. These results prove that AlphaFold combining phylogenetic analysis is a promising solution for complex gene family classification.